Halophyte Nitraria billardieri CIPK25 mitigates salinity-induced cell damage by alleviating H2O2 accumulation - Lu, Lu; Wu, Xinru; Wang, Pengkai; Zhu, Liming; Liu, Yuxin; Tang, Yao; Hao, Zhaodong; Lu, Ye; Zhang, Jingbo; Shi, Jisen; Cheng, Tielong; Chen, Jinhui (Frontiers in Plant Science, 2022)
The plant-specific module of calcineurin B-like proteins (CBLs) and CBL-interacting protein kinases (CIPKs) plays a crucial role in plant adaptation to different biotic and abiotic stresses in various plant species. Despite the importance of the CBL-CIPK module in regulating plant salt tolerance, few halophyte CIPK orthologs have been studied. We identified NbCIPK25 in the halophyte Nitraria billardieri as a salt responsive gene that may improve salt tolerance in glycophytes. Sequence analyses indicated that NbCIPK25 is a typical CIPK family member with a conserved NAF motif, which contains the amino acids: asparagine, alanine, and phenylalanine. NbCIPK25 overexpression in salt-stressed transgenic Arabidopsis seedlings resulted in enhanced tolerance to salinity, a higher survival rate, longer newly grown roots, more root meristem cells and less damaged root cells in comparison to wild type. H2O2 accumulation and malondialdehyde content both deceased in NbCIPK25-transgenic plants under salt treatment. Furthermore, their proline content, an important factor for scavenging reactive oxygen species, accumulated at a significantly higher level. In concordance, the transcription of genes related to proline accumulation was positively regulated in transgenic plants under salt condition. Finally, we observed a stronger auxin response in salt-treated transgenic roots. These results show that NbCIPK25 may improve salt tolerance by mediating the scavenging of reactive oxygen species, thereby protecting cells from oxidation and maintaining plant development under salt stress. These findings suggest the potential application of salt responsive NbCIPK25 for cultivating glycophytes with a higher salt tolerance through genetic engineering.